Fabrication of a transversal multilayer thermoelectric generator with substituted calcium manganite. Issue 12 (21st August 2017) - Reimann, Timmy; Bochmann, Arne; Vogel, Andy; Capraro, Beate; Teichert, Steffen; Töpfer, Jörg
Abstract: The sintering behavior and thermoelectric performance of Ca0.99 Gd0.01 Mn0.99 W0.01 O3 was studied, and a multilayer thermoelectric generator was fabricated. The addition of CuO as sintering additive was found to be effective for the reduction in the sintering temperature from 1300°C to about 1000°C‐1050°C. Dense samples were obtained after firing at 1050°C, whereas some porosity remained after firing at 1000°C. Samples sintered at reduced temperature exhibit lower electrical conductivity, whereas the Seebeck coefficient S  = −150 μV/K at 100°C is not affected by lowering the sintering temperature. The figure of merit is ZT = 0.12 at 700°C for samples sintered at 1300°C; ZT = 0.08 and 0.03 were obtained for multilayer laminates sintered at 1050°C and 1000°C, respectively. A transversal multilayer thermoelectric generator (TMLTEG) was built by stacking layers of substituted CaMnO3 green tapes, and printing AgPd conductor stripes onto the thermoelectric layers at an angle of 30° relative to the direction of the heat flow. The multilayer stack was co‐fired at 1000°C. The TMLTEG has a power output of 2.5 mW at ∆ T = 200 K in the temperature interval of 25°C‐300°C. A meander‐like generator with larger power output comprising six TMTEGs is also presented.